2018
DOI: 10.1016/j.scitotenv.2018.06.074
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of origins and contents of Organically Bound Tritium (OBT) and 14C in the sediments of the Rhône watershed

Abstract: Tritium (H) and Carbon-14 (C) are radionuclides of natural (cosmogenic) origin that have also been introduced into the environment by humans since the middle of the last century. They are therefore not compounds that have only recently been released into the environment and they do not pose a recognized health threat due to their low radiotoxicity. However, they hold an important place among current concerns because they are being discharged into the environment by the nuclear industry in large quantities comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 36 publications
1
24
1
Order By: Relevance
“…24 Bomb pulse 14 C from nuclear testing activities contributed large amounts of bomb pulse 14 C in the late 1960s but the levels of 14 C in the youngest MWMF tree core tissues are indicative of another more recent source of 14 C which we attribute to irrigation with 14 C-contamined pond water. It has been demonstrated that in the absence of newer sources of 14 C contamination, the levels of 14 C in more recent tree ring tissue and the atmosphere should continue to decrease with time due to the radioactive decay of 14 C to stable 14 N and intensive atmospheric mixing 22,26 but we do not observe this in the tree tissues that formed during the ~20-year irrigation period.…”
Section: Carbon-14 In Pond Water Tree Soil and Leaf Littercontrasting
confidence: 73%
See 1 more Smart Citation
“…24 Bomb pulse 14 C from nuclear testing activities contributed large amounts of bomb pulse 14 C in the late 1960s but the levels of 14 C in the youngest MWMF tree core tissues are indicative of another more recent source of 14 C which we attribute to irrigation with 14 C-contamined pond water. It has been demonstrated that in the absence of newer sources of 14 C contamination, the levels of 14 C in more recent tree ring tissue and the atmosphere should continue to decrease with time due to the radioactive decay of 14 C to stable 14 N and intensive atmospheric mixing 22,26 but we do not observe this in the tree tissues that formed during the ~20-year irrigation period.…”
Section: Carbon-14 In Pond Water Tree Soil and Leaf Littercontrasting
confidence: 73%
“…17 In addition to T, carbon-14 ( 14 C) is another radionuclide that is sometimes found in contaminated areas and its levels have been measured in tree rings. 22,23,24,25,26 These studies suggest tree ring 14 C levels can be fairly representative of historic 14 C releases from nuclear reactors as well as from nuclear weapons testing.…”
Section: Introductionmentioning
confidence: 79%
“…This shows the persistence of tritium initially integrated into the organic matter within these matrices. [1], [3], [5], [6]. Another study in Qinshan Nuclear Power Plant, China, showed that for soils collected at ± 2 km from the nuclear power plant, there is a correlation between NE-OBT and HTO ratio in soil samples.…”
Section: B Organic Bound Tritium (Obt)mentioning
confidence: 97%
“…Because tritium is part of the organic matter cycle, OBT is accumulated in organic matter storage media, especially in the sediments of streams and rivers. [6]. Tritium can persist in both terrestrial and aquatic environments according to the recycling rates of organic matter.…”
Section: B Organic Bound Tritium (Obt)mentioning
confidence: 99%
See 1 more Smart Citation